The Apollo murders : a novel - Hadfield, Chris, 1959- (Mulholland Books, Little, Brown and Company, 2021)
In the year 1973, NASA launches Apollo 18, a space mission which has been tasked with stopping a secret Soviet space station which has been spying on America.